PERBEDAAN FORGIVENESS DITINJAU DARI TIPE KEPRIBADIAN PADA REMAJA DI YAYASAN AL-HIDAYAH MEDAN: Forgiveness, tipe kepribadian - Lidia Fandini (Psikologi Prima, 2019)
This study aims to knowing forgiveness differences of reviewed from types personality consisting from introvert and eksrovert is intended to teenagers in AL-Hidayah High School Medan. Forgiveness (forgiveness) is set motivation for change someone for not reply revenge who sourced from interpersonal relations, develop feeling, mind and relationships positive with people who have do deed not fun. This type of research is a quantitative research that uses survey research techniques because in this study found a difference between the two sample. Data collection method uses questionnaire/likert scale. The hypothesis in this study is that there are differences in forgiveness in terms of introverted and extroverted personality types in adolescents. The sample of this study amounted to 60 students of AL-Hidayah High School Medan. The respondents were given two scales, namely the forgiveness scale which aims to see how high forgiveness in adolescents and the scale of personality type aims to find out the personality tendencies possessed by respondents. Furthermore, data analysis uses t-test. Based on the analysis of research data, obtained significant results 0,837 with p > 0,05. It can be seen from the analysis of the distribution of normality tests that the mean empirical forgiveness in the introverted personality type is 82,73 and forgiveness in the extroverted personality types is 109,33. So it can be concluded that extroverted personality types have the highest forgiveness, compared with introvert.It is known that the level of forgiveness in adolescents in terms of personality type has a high category because the hypothetical mean (90.0) is smaller than the empirical mean (96.03) and exceeds 2 SD numbers namely 17.56 + 17.56 = 35.12. Based on the results of the study,the hypothesis can be accepted.